AKTIVITAS CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI UPAYA DALAM MENINGKATKAN CITRA PERUSAHAAN (STUDI PADA PT ENERGI MEGA PERSADA BENTU & KORINCI BARU DI PEKANBARU) - ANDRAINA, SENA; AWZA, RUSMADI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Corporate Social Responsibility or CSR is about commitment, contribution and awareness to public company. As one of strategy to increase corporate image is to set up and carry out CSR activities are on target. PT EMP Bentu & Korinci Baru as one of the companies active in the field of oil and gas in the city of Pekanbaru, trying to realize it with focus to carry out CSR activities in several operational areas. This research aims to find out how CSR activities in the run PT EMP Bentu & Korinci Baru, and knowing the constraints of PT EMP Bentu & Korinci Baru in carrying that CSR activities. This research used qualitative methods with a descriptive approach. The research was conducted at PT EMP Bentu & Korinci Baru, Jl. Jendral Sudirman No 395, Pekanbaru. With the object of research is the CSR activities of PT EMP Bentu & Korinci Baru and research subject which all informants that meet the needs of this research, both internally and externally through purposive sampling . Data collection techniques in this research is observation, interviews and documentation. The results of this research are that run the company’s CSR activities in several aspects of life. That is the economic, health, environtment, and infrastructure is related to the role of Public Relations Officer and CSR Officer. CSR activities that run the company are prepared in accordance with need and condition of public (both human resources and resources of the village) and the capability of the company itself. By carryng out CSR activities as an effort to increase corporate image, PT EMP Bentu & Korinci Baru has been able to create good impression on the community and attract public confidence. In carrryng out CSR activities, there are a number of constraints such as, the lack of CSR officer, the limited budget and the lack of independence of the community, so that the CSR activities undertaken have not been up evenly in various aspects.Keyword: Corporate Social Responsibility, Activities, Corporate Image